Customer Satisfaction: In Relationship With Product Quality To Customer Loyality - Adia Azza Ilfana; M. Trihudiyatmanto (Jamasy: Jurnal Akuntansi, Manajemen dan Perbankan Syariah, 2022)
Objective - The purpose of this study was to identify the factors that influence customer loyalty at the Afashion Store Wonosobo. The formulation of the problem in this study is that customer loyalty at the Afashion Store is still quite volatile and there are also differences in research results. The existence of these different research results, the researcher offers a concept by providing a mediating variable, namely customer satisfaction. Methodology - This research was conducted at the Afashion Store Wonosobo. The type of research used is a research model with a quantitative approach. The sample used as many as 108 respondents with a sampling technique that is non-probability sampling. This research was conducted using SEM (Structural Equation Modeling) which is operated through the AMOS program. Results - The results of this study are that product quality affects customer satisfaction, product quality affects customer loyalty, customer satisfaction affects customer loyalty, and product quality affects customer loyalty mediated by customer satisfaction. Implication - This research is used as input for policy makers (Marketing Managers) as material for determining marketing strategies related to building customer loyalty through product quality by measuring consumer satisfaction.